TECHNO-ECONOMIC ASSESSMENT OF A 25 MW SOLAR PHOTOVOLTAIC SYSTEM FOR ELECTRICITY GENERATION IN EFFURUN-WARRI, NIGERIA - MUSHAFAU OSHUNDAIRO; JOSEPH OYEKALE (Journal of Engineering Studies and Research)
This paper was aimed at the techno-economic feasibility assessment of a 25 MW solar photovoltaic (PV) system for electricity generation in Effurun-Warri, Nigeria. The system advisor model (SAM) software was used to design and simulate the solar PV modules for power generation. Furthermore, the standard and validated models inbuilt in the SAM software were employed to analyze the techno-economic performance of the system and the energy losses. Results showed that the extent of energy losses considered in the design of the PV system had significant effects on system performance. For the 25 MW system assessed in this study, the highest monthly energy production was obtained at 3.9 GWh in January and the lowest at 1.9 GWh in July. Also, the total annual energy produced by the PV system was observed to depreciate as the system ages, with about 12% of the initial annual energy production expected to be lost after 25 years of system operation. The obtained capacity factor (12.1 %) and the performance ratio (0.75) revealed that the PV system in its current design would be inadequate to match the energy demand profile of Effurun-Warri, Nigeria. Additionally, the levelized cost of electricity (LCOE) was obtained as 0.65 cents/kWh for the system, which is about 85% higher than the current price of electrical energy in Southern Nigeria. Moreover, a negative net present value (NPV) was obtained for the plant, all indicating that the cost of investment would not be offset during the lifetime of the system, and the project would therefore not be profitable in its current design.